The multifaceted role of brood communication in wasp societies - Rafael Carvalho da Silva; Fabio Santos do Nascimento; Cintia Akemi Oi (Current Research in Insect Science)
The family Vespidae represents a key group to understand the evolutionary trajectory of social behavior in insects, as these wasps display the entire spectrum of social behaviors, from solitary to highly eusocial. The evolution of eusociality likely depended on a coordinated communication system, with chemical communication being suggested as the most commonly used among social insects. Chemical communication provides information about colony identity and an individual's identity, sex and caste, and can help resolve intracolonial conflicts. Parallel to the communication observed in adult-to-adult interactions, several reports have highlighted that the brood (eggs, larvae or pupae) can also act as direct or indirect sources of chemical compounds that can convey information. For example, eggs are covered with chemical substances that provide information about egg maternity and the queen's fertility. Given the increase in the past years of studies aiming to understand how brood can contribute to social dynamics, we reviewed the literature about the information conveyed by brood in wasp's nests across different levels of sociality. The main goal of this review was to synthesize the current knowledge and provide new venues of research. We addressed five main subjects (1) brood mediated conflicts and underlying mechanisms, (2) brood parasitism, (3) hydrocarbon cues covering brood, (4) juvenile hormone influencing brood scent and (5) other modes of communication used by brood.